EVALUATION OF BUSINESS STRATEGIES OF MOBILE GAME PUBLISHERS IN INDIA - Chandar, Venkat (Digital Repository of Theses, 2023)
This research is being conducted to explore and understand how certain Indian game developers achieved success through profitability and sustainability. The central question posed is: What are the business strategies and practices of start-up companies to build a profitable business in the mobile game industry? The goal is to analyse data from interviews conducted with founders of Indian start-ups in the mobile game industry and create a theoretical framework for future entrepreneurs in the same space to increase the chances of their success. The study used a qualitative research design by conducting semi-structured interviews over Zoom, Skype, email and face to face based on the life experience of the interviewees. Observation techniques and the interviewees responses were gathered to generate data from a target population of six candidates holding key positions in the business. Interviewees ranged from mid-senior to executive roles including ownerviii promoters. All interviewees who participated in the study were from India and engaged in the business of mobile gaming. An abductive approach was applied to the study, and themes were formed after the data from the interviews was analysed. The findings showed that the preferred business model for game development businesses in India is the free-to-play model. The primary problems for a business in the mobile games industry in India faced were personnel, capital, and lack of a support system, in that order. The major methods that these businesses achieved sustainability was through constantly building additional revenue sources, innovation and pivoting at the right time. The key learnings from operating a game development business in India were to gain a competitive advantage, work with the community and be metric focused. The results of the study were compared to those of Klimas (2017), Waller (2015) and Baghbaniyazdi et. al (2017), and extended the findings and results of the same. The findings of this study may be used by existing and new businesses as a reference in their own journey towards being profitable and then sustainable. By doing so, they will be able to contribute to the country’s economy by creating jobs, absorb talent, and potentially create India’s first billion dollar pure-play game.